Quantitative Pupillometry for Detection of Intracranial Pressure Changes During Head-Down Tilt - Soeken, Timothy A; Alonso, Al; Grant, Aaron; Calvillo, Eusebia; Gutierrez-Flores, Barbara; Clark, Jonathan; Donoviel, Dorit; Bershad, Eric M (Aerospace medicine and human performance, 2018)
There is a need to develop noninvasive methods to monitor intracranial pressure (ICP). Pupillary reactivity decreases in patients with elevated ICP with demonstrated cerebral edema. We sought to determine whether pupillary reactivity is affected when ICP is elevated in the absence of brain edema. Healthy subjects and individuals with idiopathic intracranial hypertension (IIH) underwent pupillometry in different positions (upright, supine, and head-down tilt) and during different physiological maneuvers. A separate group of healthy subjects were tested in the upright resting position only. The pupillary dynamics were measured with a pupillometer. Healthy and IIH subjects were enrolled. In the healthy subjects the change from upright to head-down tilt led to a Neurological Pupil Index (NPI) decrease from 4.30 to 4.12, while maximum pupil size and minimum pupil size increased from 4.74 to 5.19 and 3.04 to 3.44, respectively. In the IIH group the maximum pupil size, minimum pupil size, and latency increased in magnitude with a decline in head tilt. The mean NPI of IIH subjects, 4.37, was greater than the healthy mean, 4.25. Also, the mean IIH Max and Min, 5.02 and 3.25, were greater than the healthy mean, 4.62 and 2.92. We observed changes in the pupillary reactivity in all subjects based on changes in position and task. There were also differences between the healthy and IIH subjects. This is consistent with our hypothesis that elevated intracranial pressure may result in decreased pupillary reactivity even in the absence of brain edema.Soeken TA, Alonso A, Grant A, Calvillo E, Gutierrez-Flores B, Clark J, Donoviel D, Bershad EM. Quantitative pupillometry for detection of intracranial pressure changes during head-down tilt. Aerosp Med Hum Perform. 2018; 89(8):717-723.